Recovery of phosphorus from domestic wastewater with water lettuce (Pistia stratiotes) and water hyacinth (Eichhornia crassipes) - Jerry Ho, Ussan (Universiti Malaysia Sarawak, UNIMAS, 2007)
The efficiency of two floating macrophytes (water lettuce and water hyacinth) to remove phosphorus from wastewater and recover the phosphorus through composting and ashing of the plants was studied. Experiments were conducted using domestic wastewater and both phosphorus content in the wastewater and leaf and roots of both plants were studied. The water parameters evaluated for in this experiment were water pH, Dissolved Oxygen (DO), temperature and phosphorus content. In terms of percent reduction of phosphorus from wastewater, water lettuce showed a better efficiency (55.65%) compared to water hyacinth (45.29%). As for the recovery process from plant tissue, composting of water lettuce’s and water hyacinth’s leaves and roots gave lesser percentage of recovery. On the other hand, the ashing of water lettuce’s leaves and roots have showed 139% and 206% recover respectively whereas for water hyacinth the recoveries are 141% and 116% respectively for leaves and roots. Therefore, the ashing of these aquatic macrophytes could become possible to recover phosphorus in the form of fertilizer for the agricultural industry.